Waterpipe (hookah) tobacco use in pregnancy: Use, preferences, and perceptions of flavors - Stroud, Laura R. (Tob Control, 2019)
OBJECTIVE: Waterpipe tobacco (WPT; hookah) use is common in pregnant and reproductive-age women. Sweet flavors contribute to the appeal of WPT and are a potential regulatory target. This study investigated use, preferences, and perceptions of WPT flavors in pregnant WPT users, and the impact of flavor preferences on preconception/prenatal WPT use and exposure biomarkers. METHODS. 58 pregnant WPT users (mean age=27 years) completed a detailed interview regarding their WPT flavors use, preferences, and perceptions. Biomarkers of nicotine and carcinogen exposure (e.g., cotinine, benzene, butadiene) were also collected. RESULTS: 55% of participants were dual/poly WPT users (i.e., reported use of one or more other tobacco products in addition to WPT). Pregnant WPT users reported nearly exclusive use of flavored WPT, with greater use of menthol/mint (68%) followed by fruit flavors (48%) (P<.001), and greater preferences for fruit followed by menthol/mint flavors (Ps<.05). Harm perceptions did not differ among flavors. Compared to dual/poly WPT users, WPT-only users reported more total WPT use events, greater use of and preference for menthol/mint flavored WPT (Ps<.001), and decreased exposure biomarkers (Ps≤.040). Preference for menthol/mint and fruit flavors predicted more flavored WPT use events during preconception and pregnancy; preference for menthol/mint predicted detectable cotinine and benzene levels but not butadiene. CONCLUSIONS: This is the first study of WPT flavor use, preferences, and perceptions in pregnant women. Use of and preference for menthol/mint and fruit WPT flavors in this vulnerable population could be considered in regulating WPT flavors to protect the health of women and children.